Methane production enhancement from Tetraselmis biomass co-digestion using frying oil residue as co-substrate and ultrasonication as pretreatment - Firas, Feki (2023)
Tetraselmis sp. microalgae biomass co-digestion with frying oil residue was investigated without or with an ultrasonication pretreatment to enhance methane production. Interestingly, compared to untreated Tetraselmis biomass, sonication pretreatment using specific energy of 1.6 kJ/g VS significantly improved specific methane production by 60.5%. However, increasing specific energy sonication to 3.2 kJ/g VS decreased the positive energy balance of whole process from 8.6 to 5.5 ± 0.3 kJ/g VS. Furthermore, it was demonstrated that the correction of the C/N ratio with frying oil waste coupled to the sonication of Tetraselmis biomass resulted in the highest methane yield of 443.7 ± 6.4 ml CH4/g VS and highest energy gains of 14.1 ± 0.2 kJ/g VS. This study proved the presence of a complementary effect between the co-digestion of Tetraselmis biomass with frying oil and the sonication pretreatment on specific methane production and energy recovery. Low ultrasonication specific energy is recommended as pretreatment process before Tetraselmis biomass anaerobic digestion.